PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PT. RADIO ELGANGGA - Nurdianah, Dinda; Rony, Zahara Tussoleha; Sari, Rycha Kuwara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to determine the influence of transformational leadership style, physical work environment and work discipline on employee job satisfaction at PT. Elgangga Radio. The type of research used is quantitative research using a saturated sample which uses all members of the population as a sample, totaling 36 employees. PT. Elgangga Radio. The data analysis method uses SEM-PLS and the data is processed using SmartPLS 4.0. The results of this research show that (1) The transformational leadership style has a positive and significant effect on employee job satisfaction at PT. Elgangga Radio with t-statistical results of 4.126 > 1.96 and p-values 0.00 < 0.05 (2) The work environment has a positive and significant effect on employee job satisfaction at PT. Elgangga Radio with t-statistical results of 8,930 > 1.96 and p-values 0.00 < 0.05 (3) Work discipline has a positive and significant effect on employee job satisfaction at PT. Radio Elgangga with t-statistical results of t-statistical values of 2,644 >1.96 and p-values of 0.009<0.05 and (4) Transformational leadership style, physical work environment and work discipline simultaneously influence employee job satisfaction at PT. Elgangga Radio..